2023
DOI: 10.1186/s12885-023-11715-3
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 inhibitors combined with paclitaxel and cisplatin in first-line treatment of esophageal squamous cell carcinoma (ESCC): a network meta-analysis

Jia Zhao,
Simeng Zhang,
Xiaoyu Guo
et al.

Abstract: Background The combinations of PD-1 inhibitors with paclitaxel/cisplatinum (PD-1 + TP) and fluoropyrimidine/cisplatinum (PD-1 + FP) both have been shown to improve overall survival (OS) and progression-free survival (PFS) in patients with previously untreated, advanced esophageal squamous cell carcinoma (ESCC). However, there is no consensus on which chemotherapy regimen combined with PD-1 has better efficacy. To deal with this important issue in the first-line treatment of patients with ESCC, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Different chemotherapy schemes may have different antitumor efficacies. In a meta-analysis by Zhao J., PD-1 inhibitors with paclitaxel/cisplatinum were superior to fluoropyrimidine/cisplatinum ( Zhao et al, 2023 ). Several studies reported that taxane induces immunogenic cell death of cancer cells and causes various immunogenic actions, which creates favorable conditions to enhance the immune response of PD-1 inhibitors ( Chan and Yang, 2000 ; Garnett et al, 2008 ; Galluzzi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different chemotherapy schemes may have different antitumor efficacies. In a meta-analysis by Zhao J., PD-1 inhibitors with paclitaxel/cisplatinum were superior to fluoropyrimidine/cisplatinum ( Zhao et al, 2023 ). Several studies reported that taxane induces immunogenic cell death of cancer cells and causes various immunogenic actions, which creates favorable conditions to enhance the immune response of PD-1 inhibitors ( Chan and Yang, 2000 ; Garnett et al, 2008 ; Galluzzi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The breakthrough in understanding immune checkpoints and the subsequent advancement of drugs, particularly monoclonal antibodies targeting programmed cell death protein 1/programmed cell death ligand 1 (PD-1/PD-L1), represents a pivotal moment in the landscape of cancer immunotherapy [ 384 ]. These treatments have exhibited robust and sustained antitumor effects across a spectrum of cancer types [ 385 , 386 , 387 ]. However, the challenge of a notably small response rate remains a significant bottleneck for anti-PD-1/PD-L1 therapies, aggravated by the absence of precise molecular markers for patient selection [ 388 , 389 , 390 ].…”
Section: Current Approaches In the Therapeutics For Targeting Tgf-β I...mentioning
confidence: 99%